Policy evolution of solid waste management in Malaysia - Agamuthu, Pariatamby; Victor, Dennis (2011)
This paper seeks to examine the policy evolution of solid waste management in Malaysia and to determine its challenges and opportunities by assessing policy gaps, trends and stakeholders perception of solid waste management in Malaysia. Malaysian solid waste generation has been increasing drastically where solid waste generation was projected to increase from about 9.0 million tonnes in 2000 to about 10.9 million tonnes in 2010, to about 12.8 million tonnes in 2015 and finally to about 15.6 million tonnes in 2020 though national recycling rate is only about 3-5 %. This projected increasing rate of solid waste generation is expected to burden the country’s resources and environment in managing these wastes in a sustainable manner. Solid waste management policies in Malaysia has evolved from simple informal policies to supplementary provision in legislation such as the Local Government Act, 1976 and the Environmental Quality Act, 1974 to formal policies such as the National Strategic Plan for Solid Waste Management (NSP) 2005, Master Plan on National Waste Minimization (MWM) in 2006, National Solid Waste Management Policy 2006 and the Solid Waste and Public Cleansing Management Act (SWMA) 2007. Policy gap analysis indicates challenges in the area of policy implementation potentially due to lack of political will, weak stakeholder acceptance and policy impracticality due to direct adoption of policy practices from developed countries while potential opportunities are in the area of legislation for mandatory recycling and source separation as well as government green procurement initiatives. In conclusion, policy evolution of solid waste management in Malaysia may be shifting from a focus on basic solid waste management issues of proper collection, disposal and infrastructure requirements towards sustainable waste management.